Emotional Face Identification in Youths With Primary Bipolar Disorder or Primary Attention-Deficit/Hyperactivity Disorder - Seymour, Karen E. (J Am Acad Child Adolesc Psychiatry, 2013)
OBJECTIVE: Bipolar disorder (BD) and attention-deficit/hyperactivity disorder (ADHD) are often comorbid or confounded; therefore, we evaluated emotional face identification to better understand brain/behavior interactions in children and adolescents with either primary BD, primary ADHD, or typically developing controls (TDC). METHOD: Participants included individuals 7 to 17 years of age (overall sample mean age 12.40 ± 3.01 years), with “narrow-phenotype” pediatric BD (n = 30) or ADHD (n = 38), or typically developing controls (TDC) with no psychiatric disorders themselves or in their first-degree relatives (n = 41). In the BD group, comorbid diagnoses were allowed; however, youth in the ADHD group were excluded for comorbid mood or anxiety disorders. Patient groups were not excluded for psychotropic medication use. Emotional face identification was assessed using the computerized Diagnostic Analysis of Non-Verbal Accuracy (DANVA). RESULTS: Participants with BD made significantly more identification errors on child happy faces than either TDCs (p = .03) or participants with ADHD (p = .01). Furthermore, youth with BD (0.33 ± 0.55) were more likely than youth with ADHD (0.11 ± 0.31) to make errors on low-intensity child happy faces (p = .05) but not high-intensity happy faces (p = NS). Participants with BD and ADHD made significantly more total errors in child face labeling than did TDCs, although participants with BD and ADHD did not differ from one another. CONCLUSION: Our data suggest that youths with BD have specific alterations in emotional face identification of happy faces, an important finding that supports theories that response to positively valenced emotional stimuli may be especially salient in BD. Clinical trial registration information—Brain Imaging and Computer Games in Children With Either Bipolar Disorder, ADHD, Anxiety or Healthy Controls (BBPP); http://clinicaltrials.gov/; NCT01570426.